Al Qur’an dan Wawasan Ekologi Perspektif Maqashid Syari’ah - binti Abdul Rahman, Waheeda (STAINI Press, 2023)
Natural change is a change that occurs in natural systems on Earth, both through natural processes and human intervention. The worsening global natural conditions cannot be separated from various problems ranging from garbage, tree felling, and air pollution due to industrial or transportation activities as the main cause of the environmental crisis. The basic principle of ecology is to maintain, utilize and preserve the environment for the lives of future generations. Islam through its Qur'anic verses, makes guidelines for humans how to use and maintain the environment, so that the survival of this nature will be guaranteed. The writing of this article, using qualitative methods with descriptive data analysis analysis. Primary data is obtained from verses of the Qur'an, while secondary data from various references that are related to the theme. This article finds, first, that of the many verses of the Qur'an that are assumed to be verses related to ecology, verses about the preservation of nature, far more than verses related to the use of natural resources. Second, protecting the environment (hifdz al-bi'ah) is part of hifdz al-mal, because the environment is part of the material property that becomes human wealth. Thus, caring for the environment is equivalent to preserving property, which is all part of the concept of maqashid sharia